The Use of Information Service Modules to Enhance Students' Assertive Behavior - Reynalyn Tayaban; Bai Raezza I. Guizo (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Objective: Assertive behavior is a crucial social skill that students must develop to navigate interpersonal relationships and academic challenges effectively. However, fostering assertiveness among students can be difficult due to various personal and environmental factors. This study aims to measure the improvement in students' assertive behavior through the use of information service modules. Method: The research adopts a Research and Development (R&D) approach and was conducted throughout 2023 with a sample of 30 students. Data were collected through questionnaires designed to assess levels of assertive behavior before and after the intervention. The analysis involved conducting (1) normality tests to ensure data distribution assumptions were met, and (2) dependent sample t-tests to determine the significance of changes. Result: The findings indicate a significant improvement in students' assertive behavior, demonstrating the effectiveness of the developed module-based information service. Conclusion: The study confirms that the module-based information service effectively enhances students' assertive behavior and addresses the research problem. Contribution: This research provides theoretical insights and contributes to the development of module-based information service media as an effective tool for fostering students' assertive behavior.